2004
DOI: 10.7589/0090-3558-40.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Fecal Steroid Metabolites for Pregnancy Detection Used With Single Sampling in Bighorn Sheep (Ovis Canadensis)

Abstract: We compared three fecal steroid metabolite assays for their usefulness in detecting pregnancy among free-ranging Rocky Mountain bighorn sheep (Ovis canadensis canadensis) from Bighorn Canyon National Recreation Area, Wyoming and Montana (USA) and captive bighorn ewes at ZooMontana in Billings, Montana. Fecal samples were collected from 11 free-ranging, radio-collared bighorn ewes in late January-May 2001 and from 20 free-ranging, radio-collared ewes in late March to mid-May 2002. Free-ranging ewes were monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…It has also been possible to produce hybrids between Dall sheep (O. dalli) and bighorn sheep (O. canadensis), 20 because they share oestrus cycles of approximately 28 days and a gestation period between 175 and 179 days. [21][22] A recent work on gestations between bighorn and domestic sheep has uncovered that, in these interspecies gestations, there was placental insufficiency, characterized by a significant decrease in the plasma concentration of progesterone and endothelial dysfunction characterized by an increase in plasma levels of vascular endothelial growth factor and placental insulin-like growth factor-1, as well as an overexpression of hypoxia-inducible factor-1α. 23 This work sought to confirm if the production of hybrids is viable, despite the phylogenetic distance between bighorn and domestic sheep, and if the administering of progesterone throughout these gestations could favour placental development and promote foetal growth.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been possible to produce hybrids between Dall sheep (O. dalli) and bighorn sheep (O. canadensis), 20 because they share oestrus cycles of approximately 28 days and a gestation period between 175 and 179 days. [21][22] A recent work on gestations between bighorn and domestic sheep has uncovered that, in these interspecies gestations, there was placental insufficiency, characterized by a significant decrease in the plasma concentration of progesterone and endothelial dysfunction characterized by an increase in plasma levels of vascular endothelial growth factor and placental insulin-like growth factor-1, as well as an overexpression of hypoxia-inducible factor-1α. 23 This work sought to confirm if the production of hybrids is viable, despite the phylogenetic distance between bighorn and domestic sheep, and if the administering of progesterone throughout these gestations could favour placental development and promote foetal growth.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid bias derived from changing water content, most studies analyzing fecal steroids use feces that have been lyophilized before analysis and report the steroid concentrations as nanograms per gram dry feces. However, fresh, wet fecal samples are used increasingly (see Pickard et al 2001;Schoenecker et al 2004;Monclús et al 2009;Pelican et al 2009). Although the dilutive effect of water content on fecal steroid metabolites has been proven (Monclús et al 2009), it has not been demonstrated that bias in results from wet fecal samples not collected daily is due exclusively to water content, or to the microbiological and biochemical processes during the time elapsed until sampling, or a combination of both.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep are also widely used in research as an experimental model for reproductive studies of wild ruminant artiodactyls and for human neonatology studies (3)(4)(5)(6)(7)(8)(9) . Thus, hormonal monitoring becomes essential for understanding reproductive physiology and monitoring gestational development.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal metabolites of progesterone were evaluated during the estrous cycle and pregnancy in domestic (Ovis aries) (13,14) and wild (Ovis canadensis) (5) ewes, observing a high correlation between fecal metabolites and serum progesterone levels. Additionally, Schoenecker et al (6) also evaluated progesterone and estrone fecal metabolite levels in pregnant ewes, but the hormone levels were not correlated with the serum levels.…”
Section: Introductionmentioning
confidence: 99%